A man called Otto [videorecording (Blu-Ray)] - Magee, David, 1962-; Hanks, Tom; Treviño, Mariana; Keller, Rachel, 1991-; García-Rulfo, Manuel, 1981-; Hanks, Truman; Birbiglia, Mike; Backman, Fredrik, 1981- (Sony Pictures Home Entertainment, 2023)
Based on the comical and moving New York Times bestseller, it tells the story of Otto Anderson, a grumpy widower whose only joy comes from criticizing and judging his exasperated neighbors. When a lively young family moves in next door, he meets his match in quick-witted and very pregnant Marisol, leading to an unexpected friendship that will turn his world upside-down.